2018
DOI: 10.21037/tcr.2018.07.15
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of negative costimulatory molecules B7-H1, B7-H3 and B7-H4 in the process of colorectal cancer’s evolution

Abstract: Background: We made investigations on the expression of negative costimulatory molecules B7-H1, B7-H3, B7-H4 in lesions at various stages of human colorectal cancer (CRC) evolution. We also analyzed the relevance between its expression in CRC and pathological factors in clinic and patient survival time.We finally made a result that we can ensure the clinical significance of B7-H3, B7-H4 expression and the relationship between the B7 family molecules expression.Methods: All stages of CRC were collected, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This protein acts as a negative regulatory factor in the T cell-mediated immune response in the TME, 33 which has been detected in a variety of cancers and is associated with poor clinical prognosis. 34 In CRC, high expression of B7-H4 in the tumour stroma had higher survival rate than low B7-H4 patients, 35 but because there was no significant correlation observed in cancer foci and the sample size was small, this study did not receive much attention. In the present study, we combined mRNAs expression of ICGs and clinical data from two databases to show that B7-H4 can predict survival in CRC.…”
Section: Discussionmentioning
confidence: 94%
“…This protein acts as a negative regulatory factor in the T cell-mediated immune response in the TME, 33 which has been detected in a variety of cancers and is associated with poor clinical prognosis. 34 In CRC, high expression of B7-H4 in the tumour stroma had higher survival rate than low B7-H4 patients, 35 but because there was no significant correlation observed in cancer foci and the sample size was small, this study did not receive much attention. In the present study, we combined mRNAs expression of ICGs and clinical data from two databases to show that B7-H4 can predict survival in CRC.…”
Section: Discussionmentioning
confidence: 94%
“…Investigation into the expression of B7 family of proteins in colorectal tissue has revealed that B7-H3 is lowly expressed in normal colon tissue compared to CRC tissue. This feature makes B7-H3 a potential candidate biomarker for the early diagnosis of CRC [ 16 ]. Recent studies on CRC tissue samples showed a negative correlation between the tumor-infiltrating T-lymphocyte level and B7-H3 expression [ 17 ].…”
Section: B7-h3: An Overviewmentioning
confidence: 99%
“…Studies comparing B7-H3 in the lesions of CRC at various stages, such as polyps (benign), adenomas (pre-cancerous), high-grade neoplasms (adenomas with higher risk of progressing into cancer), and cancerous tissues, reported high levels of B7H1 and B7-H3 in the early stage of CRC development. They continued to express in various stages of CRC, such as adenomas, high-grade neoplasms, and cancer [ 16 ]. However, the expression of B7-H4 was reported only in the advanced stage i.e., the CRC.…”
Section: B7-h3: An Overviewmentioning
confidence: 99%
See 2 more Smart Citations